Review on Variants in Genes Associated with Cancer Risk and Red Meat Metabolism - Samsudin, Nurulhafizah; Ramzi, Nurul Hanis; Nagaretnam, Revathi; Alex, Livy (Journal of Nutritional Therapeutics, 2013)
With the advent of human genome sequencing project, came the wave of personalized genomics. Scientists have now gone beyond scanning of individual genes and epigenetic variations that might alter an individual’s predisposition to developing complex diseases. Nutritional genomics is a science which is fast catching up. Efforts to explain the diet-gene interactions often recapitulate the effects of genetic makeup in determining the exact fate of the meal we ate last. Diet-gene interactions play a major role in the metabolism and detoxification of food-derived mutagens and carcinogens. Heterocyclic amines (HCAs), polycyclic aromatic hydrocarbons (PAHs), and N-nitroso compounds (NOCs) are a class of mutagens or carcinogens found in red and processed meat that can lead to various types of cancers. Harboring unfavourable mutations or single nucleotide polymorphisms (SNPs) involved in metabolism of HCAs, PAHs, and NOCs can promote cancers. Increasing risks of several types of cancers, such as cancer of the colorectum, breast, prostate, esophagus, and lung, have been associated with high intake of red and processed meat. We attempt to compile some of the variants based on reports published during the past five years on variations involved in red meat metabolism which aims to provide useful insight in aiding us to regulate our red meat intake to avoid spurring of cancer.